Ready or Not, Here Comes the Digitalization: Assessment of Workforce Readiness and Change Perception - Ezgi Yıldırım Saatçi; Ceyda Ovacı (Istanbul Business Research)
The digital world is an indispensable reality of the new century. While technical aspects for transformation are heavily evaluated, the readiness of human resources for digital transformation is not handled as a basic change management principle. This study aims to enrich the literature by determining the perception of the readiness for a digital change of individuals. The purpose of the study is to investigate the factors that have a direct association with the readiness of the workforce during the digitalization process. The vast majority of the digital integration efforts are aimed at increasing digital maturity levels. However, in order to ensure human resources’ participation in a digital transformation, it will be useful to measure their perception of readiness for digitalization and develop strategies that will enable participation. Therefore, this research will be a guide in the journey of digital change management of the workforce. Structural Equation modelling has been used to analyse the data. The research sample consisted of 460 participants that implement a digital restructuring process in companies. The results of the research evaluated, indicate that an individual’s readiness for digital transformation is related to their perceived self-efficacy, need for change, management support and the benefit for the organization, and they are all like wheels in a machine wheels working for a successful digital transformation of workforce.